2018
DOI: 10.3390/e20080561
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Significance of Earth’s Electric and Magnetic Field Variations Preceding Earthquakes in Greece and Japan Revisited

Abstract: By analyzing the seismicity in a new time domain, termed natural time, we recently found that the change of the entropy under time reversal (Physica A2018, 506, 625–634) and the relevant complexity measures (Entropy2018, 20, 477) exhibit pronounced variations before the occurrence of the M8.2 earthquake in Mexico on 7 September 2017. Here, the statistical significance of precursory phenomena associated with other physical properties and in particular the anomalous variations observed in the Earth’s electric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Upon analyzing this signal in natural time, it was found [2] that it conforms to the conditions suggested (e.g., see [3][4][5])) for its clarification as precursory Seismic Electric Signal (SES) activity [4,6,7]. Notably, the observed lead time of 23 days lies within the range of values that has been very recently identified [8] as being statistically significant for the precursory variations of the electric field of the Earth. Moreover, the analysis in natural time of the seismicity subsequent to the SES activity in the area revealed [2] that critical conditions were obeyed early in the morning of 18 October 2018, i.e., almost a week before the strong earthquake occurrence, in agreement with earlier findings [4].…”
Section: Introductionsupporting
confidence: 69%
“…Upon analyzing this signal in natural time, it was found [2] that it conforms to the conditions suggested (e.g., see [3][4][5])) for its clarification as precursory Seismic Electric Signal (SES) activity [4,6,7]. Notably, the observed lead time of 23 days lies within the range of values that has been very recently identified [8] as being statistically significant for the precursory variations of the electric field of the Earth. Moreover, the analysis in natural time of the seismicity subsequent to the SES activity in the area revealed [2] that critical conditions were obeyed early in the morning of 18 October 2018, i.e., almost a week before the strong earthquake occurrence, in agreement with earlier findings [4].…”
Section: Introductionsupporting
confidence: 69%
“…For these reasons, the time-series of target EQs will serve as event time-series A and the time-series of β min as event time-series B, whereas the unit of time for ∆T and τ is one day. Following a previous study [7], which employed ECA to estimate the statistical significance of Seismic Electric Signals (SES) [72,73] as EQ precursors in Greece and Japan, we focus our study in the cases where the precursory p-value is smaller than or equal to the trigger p-value. Moreover, we also focus on the cases where the precursor coincidence rate equals to unity, as in our studies there have been always observed β min before the target EQs.…”
Section: Resultsmentioning
confidence: 99%
“…This is done by comparing the empirical co-occurrence frequencies with those one may expect for a null hypothesis model, e.g., uncoupled Poisson processes [2]. ECA has already found useful applications in various disciplines from epidemiology [1] and biogeography [3] to environmental and sustainability science [4], hydrology [5,6], geophysics [7,8], or even complex network physics [2]. Here, we employ ECA together with natural time analysis (NTA) to attack a problem related with the physics behind the preparation of strong earthquakes (EQs) which are one of the deadliest natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier statistical studies [Thanassoulas and Tselentis, 1993;Ifantis et al, 1995Ifantis et al, , 1997Ifantis, 2002] show that the observation stations a certain distance from the epicenter may detect the low frequency (24±8h) component enhancement before an earthquake. Recent statistical studies [Sarlis, 2018] have also shown that the anomalous GEF phenomena are statistically significant earthquake precursors with lead times in four distinct periods: 3 to 9 days, 18 to 24days, 43 to 47days and 58 to 62 days.…”
Section: Introductionmentioning
confidence: 93%